Perubahan Sosial Masyarakat Nelayan di Kawasan Pesisir Selatan Sumatera Barat - Simanjuntak, Asnika Putri; Zulkarnain; Purbata, Ardi Gustri; Nurdin, Ibnu Phonna (Sosial Horizon: Jurnal Pendidikan Sosial, 2025)
This study examines the social and economic changes in Pesisir Selatan, West Sumatra fishing communities, which have undergone transformation due to technological developments and market dynamics. The characteristics of fishermen in this area, who are generally still traditional, use small boats and simple fishing gear, have low incomes, and are highly dependent on marine catches, making them more vulnerable to economic change. Socially, changes can be seen from the shift in fishermen's work patterns, as they are starting to adapt to digital marketing and business diversification, such as switching to the tourism sector. Economically, adopting mobile phones and social media technology allows fishermen to sell their catch directly to a broader market without relying on intermediaries, even though competition is getting tougher. However, low involvement in fishing groups is still an obstacle to increasing their competitiveness. Through field observation and in-depth interviews, this study confirms that fishermen's success in dealing with change depends on their readiness to adapt.